Segmentectomy-oriented anatomical model for enhanced precision surgery of the left upper lobeCentral MessagePerspective - Shunichiro Matsuoka, MD; Takashi Eguchi, MD, PhD; Maho Seshimoto, MD; Shuji Mishima, MD; Daisuke Hara, MD; Hirotaka Kumeda, MD; Kentaro Miura, MD, PhD; Kazutoshi Hamanaka, MD, PhD; Kimihiro Shimizu, MD, PhD (JTCVS Techniques)
Objective: To optimize surgical outcomes and minimize complications in complex segmentectomy of the left upper lobe, we investigated the topographical anatomy of the left upper lobe and developed a segmentectomy-oriented anatomical model. Methods: A state-of-the-art 3-dimensional computed tomography workstation was used to visualize the intersegmental planes and associated veins to categorize the anatomical patterns influencing surgical procedures during left upper lobe segmentectomy. This included the central vein affecting S1+2 (apicoposterior segment) segmentectomy, the transverse S3 (anterior segment) affecting S3 segmentectomy, and other venous branching patterns in 395 patients who underwent thoracic surgery at our institution. Results: The central vein was observed in 32% of the patients, necessitating access from the interlobar area after segmental artery and bronchus division. Transverse S3 incidence was 27%, revealing that only one-third of the patients required complete left upper lobe transection between S4 and S3 during S3 segmentectomy. A significant negative correlation was observed between the presence of transverse S3 and the central vein (<10% of patients with the central vein had transverse S3 and vice versa). In 6% of patients, the lingular segmental veins partially or entirely drained into the inferior pulmonary vein, potentially causing excessive or insufficient resection during surgery. Conclusions: This study offers valuable insights into the topographic anatomy of the left upper lobe and presents a segmentectomy-oriented anatomical model for complex segmentectomies. Our approach enables a more precise and individualized surgical planning for patients undergoing segmentectomy based on their unique anatomy, which could thereby lead to improved patient outcomes.